Peningkatan Hasil Belajar IPS pada Bahan Kajian Kenampakan Alam dengan Metode Pemberian Tugas di SD Negeri Penanggungan Kota Malang - Sri Sugiharti (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: This action research has an objective to describe process of implementing a task assigned method and improvement of social studies – geography with natural phenomena at SDN (state elementary school) Penanggungan Kota Malang. The data collection were using observation, interview, questionnaire, and test. The results of the research, up to third cycle, found that there were improvement of learning process implementation, students’ learning activities, and groups’ task reports. Through the task assigned method, studets will involve directly in identifying problems, finishing group tasks, discussing with other members, arranging and reporting group tasks outcomes.